KEBERTAHANAN KLENENGAN SELASA LEGEN DI BALAI SOEDJATMOKO SURAKARTA TAHUN 2009-2018 - Mustika Wati; Prasadiyanto Prasadiyanto (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2021)
The research entitled Survival of Klenengan Tuesday Legen at Balai Soedjatmoko Surakarta was motivated by the existence of an activity held at Balai Soedjatmoko. This activity aims to provide a platform for musical groups who feel marginalized. This activity is held every 35 days by inviting musical groups from various cities to ensure that musical arts and activities continue to develop and survive. Based on this background, the problems were revealed in this study. (1) What is the basic concept of the Klenengan Tuesday Legen activity at the Soedjatmoko Hall? (2) Why does the Klenengan Tuesday Legen activity persist at the Soedjatmoko Hall? This research is qualitative research using the descriptive-analytical method. The author uses the thoughts of William and Achsan (Achsan Permas et al., 2003). With this approach, we get an overview of the Soedjatmoko Balai Soedjatmoko Klenengan and the factors causing the Soedjatmoko Hall's survival. Based on observations, the involvement of the implementing management of Klenengan Tuesday Legen Balai Soedjatmoko was one of the factors driving the sustainability of the activity. The activities carried out by the management include planning, organizing, implementing, and controlling activities. Through activities based on member motivation and external stimulation, efforts are being made to maintain klenengan activities on Tuesday Legen Balai Soedjadmoko. The member's motivation is in the form of a desire to express a sense of pleasure for musical instruments gathering with people who have the same interest in the arts. Stimulation that affects the survival of Klenengan Tuesday Legen is the support from Bentara Budaya.